Pengaruh Perbedaan Benih Asal Pertanian Organik dan Konvensional Terhadap Sifat Fisiologis dan Hasil Padi Organik Kultivar Lokal dan Unggul - Mildaerizanti, Didik Indradewa, dan Prapto Yudono (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2012)
ABSTRACTThe farmers involved in Organic farming have many problems, particularly in agriculture, in terms of the provisions dealing with the cultivation of organic food which refers to SNI 6729 in 2010 in which the seed used must come from organic farming itself. In addition to the seed, organic farming requires a suitable varieties for organic conditions, suspected nutrient deficiencies, while special varieties are produced to organic land is not yet available. Research done “The Effect of differences seed origin in organic and conventional farming on the physiological and yield organic rice of local cultivars (Mentik Wangi Susu) and superior (IR-64)